Proceedings of the 4th Bandung Creative Movement International Conference on Creative Industries 2017 (4th BCM 2017) 2018
DOI: 10.2991/bcm-17.2018.71
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Golden Section Proportion Potency in Mosque

Abstract: Various mosque designs appear in Indonesia, with various shapes, with or without domes. Until now the visualization of mosque formation that mosque has domes still accepted in general. Architectural forms are part of the visual language that is bound by the rules of geometry and proportion. Historically, the proportion of the Golden Section is a mathematical comparison applied to the design process. While in design, architects often involve a sense, whether the building design has been proportional or not. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Handayani and Soewardikoen (2018) investigated the use of the Golden ratio in mosque facade design by examining three mosques. The findings suggested that the use of mathematical principles in mosque design can contribute to achieving a sense of harmony and balance in the built environment [9]. In the same way, Wafaei Baneh et al ( 2021) demonstrate how the Golden Ratio, a crucial element of sacred geometry, lies at the foundation of Islamic architecture and decoration.…”
Section: Previous Related Studiesmentioning
confidence: 94%
See 2 more Smart Citations
“…Handayani and Soewardikoen (2018) investigated the use of the Golden ratio in mosque facade design by examining three mosques. The findings suggested that the use of mathematical principles in mosque design can contribute to achieving a sense of harmony and balance in the built environment [9]. In the same way, Wafaei Baneh et al ( 2021) demonstrate how the Golden Ratio, a crucial element of sacred geometry, lies at the foundation of Islamic architecture and decoration.…”
Section: Previous Related Studiesmentioning
confidence: 94%
“…The study of geometry in architecture involves various aspects, such as its structural application, modular dimensions, and mystic meanings. It is essential to incorporate geometry in the plan and facade of buildings to claim a comprehensive understanding of this knowledge [9]. Design based on this knowledge involves accurately identifying geometric elements at different levels and their respective positions in the design, understanding the relationships between them, and utilizing composition techniques to convey their meanings [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation